Mediterranean Sea level variations: Analysis of the satellite altimetric data, 1992–2008 - Vigo, M.I.; Sánchez-Reales, J.M.; Trottini, M.; Chao, B.F. (Journal of geodynamics, 2011)
► Mediterranean SLV trend over 1992–2008 is subject to a quadratic acceleration (QA). ► The QA-model outperforms existing modeling based on linear trend. ► Allows detection of regional acceleration/deceleration in sea level changes. ► The residual low frequency SLV is driven by NAO in wintertime. ► The residual high-frequency signal variability is explained by mesoscale phenomena. Sixteen years of satellite radar altimeter data are analyzed to investigate the sea-level variation (SLV) of the Mediterranean Sea. The time evolution of the overall mean sea level of the Mediterranean Sea follows its own regional dynamics. The geographical distribution of the seasonal signal (annual and semi-annual) indicates that the major features of the Mediterranean Sea circulation are driving the highest seasonal variability, and that an eastward propagation exists between the western and eastern basins. While in previous studies the trend of SLV has been modeled as linear, in this study with a longer record of observations we found that a quadratic acceleration term is statistically significant for practically the whole basin, especially in those regions where the trend provides a significant contribution to the SLV. The inclusion of the quadratic acceleration term accounts better for the Mediterranean SLV trend, as the residual low frequency SLV in wintertime is highly correlated with NAO at zero time lag in almost the whole basin. The residual high-frequency signal variability, on the other hand, can be explained by mesoscale phenomena, such as eddies and gyres. Our comprehensive analysis of the Mediterranean SLV provides source observations for monitoring and understanding of both regular and transient phenomena.